METHODOLOGICAL APPROACHES TO MODERNIZATION PROCESSES OF THE PRODUCTIVE FORCES IN THE CONDITIONS OF EUROINTEGRATION - Popelo, Olga (Науковий вісник Полісся, 2017)
Urgency of the research. In today's turbulent world that is constantly crisis shaking, the national economy requires fundamentally new approaches to the regional development policy. The modernization of the productive forces plays dominant role in accelerating of the economic reforms. It provides new disclosure and quality enhancement of human potential, localization of economic activity based on the intensification of innovative activities and increasing of investment appeal, conservation, restoration and enrichment of natural-resource potential. Target setting. It is expedient to distinguish the principles of involvement of the productive forces in the context of current regional policy and systematize the principles of modernization of the productive forces in the conditions of Eurointegration. Actual scientific researches and issues analysis. The theoretical and practical aspects of productive forces modernization were highlighted in works of such scholars as A. Amosha, Z. Gerasymchuk, M. Butko, B. Vakulenko, V. Varnavskyy, S. Varnaliy, B. Vynnytsky, V. Geyets, B. Danylyshyn, M. Dolishniy, S. Doroguntsov, V. Zakharchenko, S. Ishchuk, E. Libanova, V. Miklovda, S. Mocherny, J. Olejnik, T. Pepa, L. Fedulova, L. Chernjuk, M. Chumachenko, A. Chukhno and others. Uninvestigated parts of general matters defining. Despite numerous studies, the modernization of the productive forces in terms of European integration requires further study and analysis. The research objective. The main goal of this work is the research and generalization of methodological approaches to the modernization processesof the productive forces in terms of European integration. The statement of basic materials. The article reveals the essence of the concept of "principles of development of productive forces". An principles involvement of the productive forces in the context of current regional policy. Systematized modernization principles of the productive forces in terms of European integration and organized grouping of the following areas: formation, functioning and development. Conclusions. In the present globalization conditions of the economy modernization in general and the productive forces particularly based on maximum involvement of the intellectual potential, implementation of new technologies and other types of innovation is the only way to overcome the crisis, ensure sustainable economic growth, improve the quality and standard of living. Consideration of proposed methodological approaches to the modernization of the productive forces in European integration will contribute to sustainable economic development and ensure its prosperity.